Avalia??o de uma abordagem de aprendizagem baseada em problemas no ensino de Programa??o Orientada a Objetos - Ribeiro, Ayala Lemos (2019)
Problems related to learning programming in undergraduate computing programs contribute to lack of motivation, failure and early abandonment of these programs. The motivation of computing students in programming courses is a relevant factor that may contribute to success in learning. This work evaluates students' motivation and learning in a teaching-learning approach to object-oriented programming in the Computer Engineering program at the State University of Feira de Santana, in an integrated curricular component of Programming of the second term of this program that uses the problem-based learning approach (PBL). This integrated component was organized into three theoretical modules addressed through lectures and an integrator module that followed the PBL dynamics. Results describe the levels of motivation in terms of attention, relevance, con dence and satisfaction, and learning in terms of student performance, all measured in both the theoretical modules and the PBL integrator module. In addition, this case study has led us to important lessons learned: the acquisition of personal, interpersonal and technical skills provided by the approach; the bene ts of integrating knowledge through more authentic experiences and a more disciplined practice of software production; the need for careful problem planning; the main difficulties faced by instructors to manage the course; the challenges students face to develop their skills; and and con dence as a prime motivational factor for learning. This work contributes to the knowledge in the eld of computing education, more speci cally in evaluating motivation and learning of computing students who learn through the PBL approach, potentially allowing to advance in the dissemination and effectiveness improvement of this approach in the eld of computing.